1981
DOI: 10.1002/ijc.2910270408
|View full text |Cite
|
Sign up to set email alerts
|

Special report animal species in which n‐nitroso compounds induce cancer

Abstract: In reviews on the carcinogenicity of N-nitroso compounds (NC) the number of animal species in which these compounds induce cancer is understated. In recent years additional species have been used in experiments. Tumours have been induced by NC in 39 species which belong to 36 genera, 25 families, 17 orders and five class of animals. The names of these taxa are presented in Latin and the common names of species are given in English, French and German. The carcinogenic action of eight NC in various species is ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
124
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(125 citation statements)
references
References 8 publications
1
124
0
Order By: Relevance
“…N-Methyl-N-nitrosourea (MNU) is a direct acting alkylating agent that does not require metabolic activation by the P-450 system and is known to be a potent mutagen (3,29), teratogen (24,44), and carcinogen (2,7). We have demonstrated that MNU specifically targets retinal photoreceptor cells causing retinal degeneration when administered to adult laboratory animals (25,28,40,47) or results in retinal dysplasia when administered in the neonatal period (26,27) in various animal species.…”
Section: Introductionmentioning
confidence: 99%
“…N-Methyl-N-nitrosourea (MNU) is a direct acting alkylating agent that does not require metabolic activation by the P-450 system and is known to be a potent mutagen (3,29), teratogen (24,44), and carcinogen (2,7). We have demonstrated that MNU specifically targets retinal photoreceptor cells causing retinal degeneration when administered to adult laboratory animals (25,28,40,47) or results in retinal dysplasia when administered in the neonatal period (26,27) in various animal species.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, it has been hypothesized that cigarette smoking may be involved in the etiology of glioma, 5 based on evidence that N-nitroso compounds, such as those found in cigarette smoke, have been shown to induce glioma in rats when administered intravenously. 6,7 The epidemiologic literature regarding cigarette smoking and brain cancer risk is based primarily on case-control studies, all of which have found no association with ever smoking. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] A recent cohort study by Efird et al, 22 however, observed an increased risk of glioma in those who reported smoking greater than 2 packs of cigarettes per day.…”
mentioning
confidence: 99%
“…N-nitroso compounds (NOCs) can induce cancer in multiple organs in at least 40 different animal species, including higher primates [106][107][108]. In in vitro studies on human liver slices, the mechanism of action was shown to be nucleic acid alkylation [109].…”
Section: N-nitrosoglyphosate and N-nitrososarcosinementioning
confidence: 99%